Sistem Informasi Setoran Wajib Jemaat Menggunakan Framework Codeigniter - Filia Meitri Alelo; Remuz MB Kmurawak; Mingsep Rante Sampebua (ISB Atma Luhur, 2021)
Klasis GKI Sentani is part of the GKI Denomination which regulates churches in the Jayapura (Sentani) Regency area. One of the tasks of the Klasis is the monitoring and evaluation of the Setoran Wajib Jemaat (SWJ). Each Church is required to collect offerings cumulatively each month. The obstacle faced in financial management in the Klasis Sentani environment is the budget processing system which is manual, where donations are deposited to Klasis by attaching proof of deposit. this makes the process of collecting donations an inefficient routine. Including the documentation process that looks not up-to-date and the difficulty in publishing the results to the congregation at Klasis Sentani. This study aims to facilitate the reporting of mandatory deposits for the classic GKI Sentani congregation, namely by creating an information system for the congregation's mandatory deposit. The development of the software system uses the Waterfall method, with the Unified Modeling Language as the system modeling language. This system has been implemented and makes it easier to manage finances for the church treasurer and classics. Financial information can also be viewed transparently on the page provided and can be accessed by the congregation.